HEART RATE VARIABILITY IN ASSESSMENT OF CLINICAL STATUS, FUNCTIONAL CONDITIONS AND PROGNOSIS IN HEART FAILURE - Y. A. Vasyuk; E. Y. Shupenina; E. N. Yuschuk; M. K. Serova (Столичная издательская компания, 2016)
Data about heart rate variability analysis in healthy people and patients with chronic heart failure are reviewed. Prognostic value of time-domain and spectral measures is mentioned. Influence of standard therapy on heart rate variability is described.